The effect of menopause on chronic periodontitis - Zulkeple, Hafizul Taufiq; Zahuri, Muhammad Khairulanwar; Ridzuan, Taufik Firdaus; Al-bayati, Lina Hilal; Faisal, Ghasak Ghazi; Mustafa Al-Ahmad, Basma Ezzat (Ectodermal Dysplasia Group-Turkey, 2016)

(untitled)
The aim of the present study is to investigate the severity of periodontal destruction among Malaysian women based on their menopausal status. The study was conducted as a case–control study in which 50 systemically healthy women who were diagnosed with chronic periodontitis were included. Based on their menstruation history, they have been divided into two groups: control group includes 25 women undergoing normal menstrual cycle, while the test group includes 25 postmenopausal women. The clinical periodontal parameters were recorded, and the severity of the periodontal destruction was evaluated clinically according to the clinical attachment loss. There were no significant differences between participants of the control and test groups in the percentages of sites with the presence of plaque and bleeding on probing (p>0.05). On the other hand, significant differences were found between both groups in their percentages of sites with clinical attachment loss of 4-6 mm (p=0.13) and number of missing teeth (p=0.20). The findings of the present study suggest that postmenopausal women have more severe periodontal destruction compared to premenopausal females